1989
DOI: 10.1088/0954-3899/15/8/002
|View full text |Cite
|
Sign up to set email alerts
|

Effective fusion barrier transmission model for heavy-ion fusion

Abstract: A new effective fusion barrier transmission model is developed. This gives a good description of the measured fusion cross sections both below and above the Coulomb barrier for a number of pairs of nuclei. The model uses only the surface region (r> RF-RB) of the heavy-ion optical potential describing the scattering data. The correlation of this approach with the direct reaction description of fusion is established. A physical interpretation for rF is indicated in terms of nucleon flux and neutron transfer time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In our calculation we set r F = 1.4 fm giving the fusion radius R F = 7.213 fm and T = ∆e = 0.75 MeV. In the application of EFB model in several cases elsewhere [9] we have found that at a given energy above V 0 B , σ F is minimum for R F ∼R B . Increasing or decreasing of R F from the optimum value gives higher values of σ F with sharper rise for values of R F >R B .…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our calculation we set r F = 1.4 fm giving the fusion radius R F = 7.213 fm and T = ∆e = 0.75 MeV. In the application of EFB model in several cases elsewhere [9] we have found that at a given energy above V 0 B , σ F is minimum for R F ∼R B . Increasing or decreasing of R F from the optimum value gives higher values of σ F with sharper rise for values of R F >R B .…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The expressions for transmission probability deduced within the framework EFB model and using the mathematical procedure of Farina [19] are used to analyze the heavy ion fusion cross section σ F of nucleus-nucleus collisions involving weakly bound unstable neutron rich projectiles namely 9 Be and 11 Li scattering on light as well as heavy stable targets. The influence of particle evaporation of the participants on the fusion process at low bombarding energies is investigated leading to the following observations: (i) When the neutron separation energy n < 5 MeV, it causes reduction in the survival probability SP of the participants and (ii) when n is very small , i.e., n < 1 MeV, along with the reduction of SP, there is reduction in the height of the potential barrier [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations